VD_FINDINFO 19/2022/EKA vom 23. August 2023 - VD Tribunal cantonal (2023)
CONTRAT SUI GENERIS, CONTRAT DE REPRÉSENTATION EXCLUSIVE | 18 CO, 19 CO, 128 al. 1 CPC (CH), 128 al. 4 CPC (CH), 59 al. 2 let. a CPC (CH)